Long-term preservation of bacteria in washed sterile sand: A 14-year study - Amina Manni; El-Houcine Ait-Ouakrim; Bouchra Belkadi; Abdelkarim Filali-Maltouf (PLoS ONE, 2026)
Background Cryopreservation and lyophilization are standard methods for preserving microbial cultures, but they are expensive and labor-intensive, creating a barrier for resource-constrained laboratories. This study evaluated the efficacy of a simple and inexpensive alternative: long-term storage in washed and sterilized sand. Methods Fourteen bacterial strains from ten genera were preserved in sealed tubes containing washed and sterilized sand at room temperature. Viability, assessed by colony-forming units (CFU/g), was quantified at inoculation and after 7 and 14 years. Phenotypic stability was evaluated by comparing the pre- and post-storage profiles for enzyme activity and stress tolerance. Results After seven years, all 14 strains remained culturable with preserved phenotypic features. After 14 years, 13 strains (93%) were viable. The highest recovery rates were observed in spore-forming Gram-positive bacteria (e.g., Bacillus sp .), indicating taxon-specific survival. Notably, the Gram-negative strain Enterobacter hormaechei remained stable with only a approximate 1.58 log₁₀ reduction over 14 years (half-life = 2.67 years). All resuscitated strains maintained their pre-storage characteristics. The distinct survival patterns for each species indicate that contamination was not the primary driver of the outcomes. Conclusion Washed and sterile sand offers a practical, low-energy matrix for long-term preservation of a diverse range of bacteria, effectively maintaining cultivability and key phenotypic attributes for over a decade. This approach is an economical preservation strategy for resource-limited laboratories and field collections.